Fair Labor Standards Act : Analysis of Economic Issues In the Debates of 1937-1938. (U.S. Congressional Research., 1989)
Analyzes major economic issues and questions in 1937-1938 debates surrounding the passage of the Fair Labor Standards Act that instituted Federal standards for minimum wages, overtime pay and child labor. Provides overview of legislative intent, and discusses questions regarding basic philosophical and policy issues, Congressional role as bargaining agent for the working poor, impact on small business, impact of minimum wages, protection of the "fair" employer, "cheap labor" and economics of regionalism, impact on agriculture, international industrial competition, special considerations with respect to labor, fears of an alien and subversive plot, and the cost of inaction.